2004
DOI: 10.1109/tmag.2004.832145
|View full text |Cite
|
Sign up to set email alerts
|

Micromagnetic Study of Domain Wall-Pinning Characteristics With Step-Like Thickness Change in Thin Film

Abstract: The pinning characteristics of a domain wall with a step-like thickness change along the wall is investigated in 0.15-to 0.5-m-thick films with an in-plane anisotropy using micromagnetic simulation based on the Landau-Lifshitz-Gilbert equation. The asymmetric Bloch wall having the structure in which the magnetostatic coupling develops between spins near the step when the wall is pinned shows the bi-directional pinning effect for magnetic fields applied along the magnetic domain. The wall energy of the pinned w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The simulation results performed by varying the shape of thickness change have suggested that the depinning field decreased as a slope becomes gentler. 6 Although observation of a negative wall depinning from …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulation results performed by varying the shape of thickness change have suggested that the depinning field decreased as a slope becomes gentler. 6 Although observation of a negative wall depinning from …”
Section: Resultsmentioning
confidence: 99%
“…5 In the previous work, micromagnetic simulation has reported that steplike thickness change along a domain wall can produce wall pinning in an in-plane magnetization thin film. 6,7 The simulation results have indicated that a bidirectional pinning effect for magnetic fields applied along the magnetic domain was obtained at the step.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations